AN INTEGRATED APPROACH IN COMMUNITY EMPOWERMENT THROUGH HEALTH EDUCATION, LOCAL PRODUCT DEVELOPMENT AND TRAFFIC SAFETY INNOVATIONS IN GEGESIK WETAN VILLAGE - Deni Yusup Permana; Rizki Akbar Sadewo; Safina Ni'mah; Nia Taniyah; Kikit Wulandari; Zeva Mahardika; Ade Alfas Bagus; Keyza Melia Putri; Indi Syahputri; Moch. Hafizd Zidny; Laviola Fiorentina; Rafa Rizqullah; Nanda Galireksa; Venus Medina Liana; Siti Nurhaliza; Ghaliyah Salsabillah; Wanda Mutya; Rafi Fadhil Athallah (Ann Publisher, 2026)
Background. Real Work Lecture (KKN) is a form of implementation of the Tri Dharma of Higher Education, which aims to encourage student involvement in community empowerment through a participatory approach and based on local needs. Aims. This service activity was carried out in Gegesik Wetan Village, Gegesik District, Cirebon Regency, with a focus on increasing public knowledge in the health sector, empowering the local economy through strengthening MSMEs, and improving environmental safety. Methods. The method used in this activity is a qualitative descriptive approach with a participatory method through the stages of field observation, problem identification, program design, and implementation of activities involving the community and village government. Result. The programs implemented include socialization on anti-bullying, juvenile delinquency, skin health, Clean and Healthy Living Behavior (PHBS), stunting prevention, prevention of Dengue Hemorrhagic Fever (DHF) and chikungunya, and reproductive health education in schools and communities. In addition, MSME empowerment is carried out through the One Village One Product (OVOP) approach, with assistance to traditional geplak food business actors in managing Business Identification Numbers (NIB), halal certification, and product identity development, including brand and logo development. Another program is community empowerment through socialization of the decile concept and training in making ecoenzymes as well as improving traffic safety through the installation of convex glass at several accident-prone road points. Conclusion. The results of the activity show an increase in public knowledge and awareness of health, an increase in the understanding of MSME actors regarding the importance of business legality and product branding, and the creation of preventive efforts to improve village traffic safety. Overall, this KKN activity makes a positive contribution to community empowerment and the sustainable development of local potential in Gegesik Wetan Village.